2014
DOI: 10.1017/s0950268814002957
|View full text |Cite
|
Sign up to set email alerts
|

Infection risk factors associated with seropositivity forToxoplasma gondiiin a population-based study in the Central Region, Ghana

Abstract: About 20-90% of the world's population has had contact with Toxoplasma gondii parasites. The aim of this study was to determine the seroprevalence and risk factors associated with T. gondii infection in the Central Region, Ghana. A community-based cross-sectional study was conducted in three selected communities. Serum samples were tested for the presence of anti-T. gondii IgG and IgM antibodies by ELISA. A serological criterion for seropositivity was a positive test result for any of the two anti-Toxoplasma I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
3
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
(54 reference statements)
5
17
3
1
Order By: Relevance
“…The odds of being infected with T.gondii was more likely occur in those consume raw meat compared to those didn't consume (AOR=5.1, 95% CI: 2.22-11.68, P:0.001) in contrast with other reports. 20,26,22 This variation in different study does not mean raw meat is not source of T.gondii infection, but this variation is due to cultural and eating habits in diverse human populations 41 and disparity of seroprevalence of T.gondii infection in meat producing animals in different countries. In this study, those handling of raw meat was protective against T.gondii infection (AOR=2.4, 95% CI: 1-5.56, P:0.049).…”
Section: Discussionmentioning
confidence: 99%
“…The odds of being infected with T.gondii was more likely occur in those consume raw meat compared to those didn't consume (AOR=5.1, 95% CI: 2.22-11.68, P:0.001) in contrast with other reports. 20,26,22 This variation in different study does not mean raw meat is not source of T.gondii infection, but this variation is due to cultural and eating habits in diverse human populations 41 and disparity of seroprevalence of T.gondii infection in meat producing animals in different countries. In this study, those handling of raw meat was protective against T.gondii infection (AOR=2.4, 95% CI: 1-5.56, P:0.049).…”
Section: Discussionmentioning
confidence: 99%
“…Also of interest in this youthful population was the burden of posterior segment disease that had caused UVI in nine participants, out of which four were attributable to toxoplasmic chorioretinitis. Epidemiological survey on a subpopulation indicates that Ghana is among the countries with a high seroprevalence rate of Toxoplasma gondii , 19 signifying a high risk to this infectious agent. The outcome of our study corroborates findings that visual impairment caused by retinal disorders in the young Ghanaian population is of public health concern.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in more than two thirds of women that acquired infection during pregnancy, no contact with any known or suspected source of infection was identified [4,5]. Many studies showed that contact with cats, touching garden soil or eating raw meat were important epidemiological risk factors [6][7][8], while other studies did not demonstrate their role in transmitting the infection [9,10]. A few studies detected some unusual predictors of being T. gondii infected, such as keeping rabbits for meat [9,10], having a dog at home [11], having mice in a house [12], eating raw shellfish [13], being in a close contact with livestock [14], and having high rate of sexual activity [15,16].…”
Section: Introductionmentioning
confidence: 99%